The Japanese Quail: A Review - Vali, Nasrollah (International Journal of Poultry Science, 2008)
The Japanese quail belongs to the order Galformes, family Phasidae, genus Coturnix and species japonica. Several aspects account for the utility of this bird. First, it has attained economic importance as an agricultural species producing eggs and meat that are enjoyed for their unique flavor. Egg production is important in Japan and Southeast Asia, while meat is the main product in Europe. Second, the low maintenance cost associated with its small body size (80-300 g) coupled with its short generation interval, (3-4 generation per year), resistance to diseases and high egg production, rendered it an excellent laboratory animal. Third, Japanese quail also is the smallest avian species farmed for meat and egg production. It has thus been used extensively in many studies. The Japanese quail is bred for egg and meat production. Few studies have been published on egg production but, reports on quail growth and body composition are numerous. Some of the estimated genetic parameters for various traits of Japanese quail were reported by several workers.